Adopting a Constraints-Led Approach to Enhance Skill Acquisition for Fast Bowlers in Grassroots Cricket - Mikael Jamil; Lewis Woolston; Simon Manthorpe; Saumya Mehta; Daniel Memmert; Allistair McRobert (Journal of Coaching and Sports Science, 2023)
In this quantitative study, a bespoke coaching drill was designed and tested over 16 weeks to improve the bowling accuracy of 6 participant seam bowlers. This experiment consisted of 6 male participants with a mean age of 19.5 ± 7.5, mean height (cm) of 184.75 ± 5.57, and mean weight (kg) of 78.05 ± 9.87. Due to the repeated measures experimental design, paired samples t-tests were conducted to assess the effectiveness of this coaching intervention and compare performances between the "control" phase and the "training" phase. Results revealed that this purposely designed coaching drill led to a significant improvement in bowling lines (p less than 0.001) with a moderate effect size and bowling lengths (p less than 0.001) with a large effect size. However, this coaching intervention did not have any significant effect on bowling discipline (p = 0.134). Evidence proves that regular repetition of exercises over a prolonged time can ultimately enhance motor skill refinement. From a practical perspective, coaches can replicate the drill introduced in this study as a means of skill acquisition and skill refinement for their seam bowlers.